The Peoples Game : Football Fandom in Zimbabwe - Chiweshe, Manase Kudzai (Book collections on Project MUSE., 2017)
This book weaves together a rich tapestry on football fandom in Zimbabwe. Based on empirical research focusing on the different dimensions of fan practices and experiences, the book is the result of multiple fieldwork processes with fans in Zimbabwe spanning a period of eight years including desk research, interviews, observation, focus group discussions and netnography. It demonstrates the nexus between social identities and supporting a sports team, highlighting that there are deeper underlying meanings and assumptions to one's support of a sporting team. Manase Chiweshe highlights the various nuances of supporting football clubs. This book provides an alternative way to understanding communities and how sport can be viewed as a serious lens into societal organisations. It offers important insights into how Zimbabweans are also engaged in leisure activities and that play is also part of their life worlds. Given the major focus on poverty, disease and conflict, African stories of intimate play and enjoyment tend to be sidelined. Soccer has the power to bring together or divide communities. In many an African context, just as in Zimbabwe, everyday ethnic and religious rivalries are played out through football matches. It is thus important to capture this space and use football as a way to heal historic and deep-seated conflicts.